TINJAUAN YURIDIS TENTANG PELIMPAHAN HAK ASUH ANAK DI BAWAH UMUR AKIBAT PERCERAIAN DI PENGADILAN AGAMA SAMARINDA - Suparmanto Suparmanto (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTDivorce is the breaking up of a legitimate marriage before the court under the conditions prescribed by the Act. With the breaking up of a marriage due to a divorce, there will be legal consequences following it, that of custody of the child born of the marriage and the power of the parent who is changed into guardianship. What the author wants analysis is what a judge should consider in giving the custody and responsibility to the father, because in reality the custody of minors is often given to the mother until the child is mature and chooses for himself whether he will go with his mother or With his father, what judge's judgment establishes the father who is entitled to take care of the child, and whether the verdict given by the judge can be canceled and custody of the child is returned to his mother.The method used in writing this thesis is a normative juridical research method. Normative juridical research is a research aimed and conducted by using the study of legislation and other written legal materials related to the writing of this thesis. The types of data used are primary legal materials and secondary legal materials. Data collection techniques used are through research judge verdict and library research, both bookubuku, legislation, documents, and so forth. Data analysis used secondary data analysis technique.The result of the verdict was found that the Judge in deciding a case saw the circumstances of the caretaker and the child to be maintained. These include economic factors, environmental factors, the behavior of the mother or father, the age of the child, the sex of the child, and the certainty of education and a decent life. But for a parent who does not get custody, it can not be prevented to meet with his child as long as it does not cause moral damage to the child later. Therefore, the Judge decided that Bapaklah as the child custody holder of the Medan District Court Ruling. 246 / PDT.G / 2012 / PN.MDN, Lubuk Pakam District Court No. 13 / Pdt.G / 2012 / PN.LP, and No.102 / Pdt.G / 2013 / PN.LP where the Mother assessed the Judge is not good if given the power of foster child of Plaintiff and Defendant. Such custody may also return to the mother through an appeal such as no. 66 / PDT / 2012 / PT.DPS which has been decided by the High Court of Samarinda  Keywords: Divorce, Child Custody.